2015
DOI: 10.1680/geng.14.00054
|View full text |Cite
|
Sign up to set email alerts
|

Twin-tunnelling-induced ground movements in clay

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Modern tunnelling methods aim to reduce ground movements arising from the construction process. In clay strata the usual method of construction is by tunnel boring machine, which allows close control of the tunnelling process; however, any movements have the potential to cause damage to existing structures at, and below, the ground surface. The construction of underground rail systems often c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The relative differences in the Volume Losses have only recently been studied (e.g. Addenbrooke & Potts, 2001;Hunt, 2005 andDivall &Goodey, 2015). These studies offer a means by which the magnitude of the increase in Volume Loss can be ascertained based on the tunnel centre-tocentre spacing.…”
Section: Tunnelling-induced Ground Movementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relative differences in the Volume Losses have only recently been studied (e.g. Addenbrooke & Potts, 2001;Hunt, 2005 andDivall &Goodey, 2015). These studies offer a means by which the magnitude of the increase in Volume Loss can be ascertained based on the tunnel centre-tocentre spacing.…”
Section: Tunnelling-induced Ground Movementsmentioning
confidence: 99%
“…These studies offer a means by which the magnitude of the increase in Volume Loss can be ascertained based on the tunnel centre-tocentre spacing. Figure 1 shows the overall trend presented by Divall & Goodey (2015) along with three case studies with some selected field measurements. These case studies (Cooper & Chapman, 1998;Cording & Hansmire, 1975;Nyren, 1998) are consistent with the experimental data supporting the relationship proposed.…”
Section: Tunnelling-induced Ground Movementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sixth paper (Divall and Goodey, 2015) is about twin-tunnelinduced ground movements in clay. The authors performed twodimensional plane strain centrifuge tests on twin tunnels at different spacing and found that the second tunnel caused greater volume loss than would be expected by superposition.…”
mentioning
confidence: 99%